2003
DOI: 10.1091/mbc.e02-09-0581
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chromatin Proteins High Mobility Group Box (HMGB) 1 and HMGB2 with Mitotic Chromosomes

Abstract: High mobility group box (HMGB) 1 and 2 are two abundant nonhistone nuclear proteins that have been found in association with chromatin. Previous studies based on immunofluorescence analysis indicated that HMGB1 dissociates from chromosomes during mitosis. In the present work, HMGB1 and 2 subcellular localization was reinvestigated in living cells by using enhanced green fluorescent protein- and Discosome sp. red fluorescent protein-tagged proteins. Contrary to previous reports, HMGB1 and 2 were shown to be pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
119
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(132 citation statements)
references
References 57 publications
11
119
1
1
Order By: Relevance
“…The relative increase of the cytoplasmic per total HMGB1 protein may, at least in part, result from the dissociation of nuclear HMGB1 into the cytoplasm during mitosis of the epithelial cells (16,51). Our previous study clearly demonstrated a greater (~1.2-fold) proliferation of lung epithelial cells in the presence of fibroblasts and conditioned medium from fibroblasts, respectively, which was less pronounced by inhibiting the basic fibroblast growth factor (bFGF) (34).…”
Section: Discussionmentioning
confidence: 97%
“…The relative increase of the cytoplasmic per total HMGB1 protein may, at least in part, result from the dissociation of nuclear HMGB1 into the cytoplasm during mitosis of the epithelial cells (16,51). Our previous study clearly demonstrated a greater (~1.2-fold) proliferation of lung epithelial cells in the presence of fibroblasts and conditioned medium from fibroblasts, respectively, which was less pronounced by inhibiting the basic fibroblast growth factor (bFGF) (34).…”
Section: Discussionmentioning
confidence: 97%
“…Thus, it is hypothesized that the close proximity of both NLSs in a resting state is disturbed by concomitant phosphorylation at the regions close to the NLSs when stimulated. In the study of HMGB2 (previously HMG2) protein, which has high sequence similarities with HMGB1, the acidic carboxyl terminus influences its retention in the nucleus (38,39). Thus, we are now studying the role of the HMGB1 acidic tail in the nuclear transport of the protein because HMGB1 and HMGB2 are not structurally and functionally the same (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Tumorzellen k ö nnen diese nat ü rliche Replikationsbeschr ä nkung ü berwinden, indem sie mit speziellen Telomerasen die Telomere wieder verl ä ngern und damit nie die kritische L ä nge unterschreiten [95,96] . HMGB1 als DNA-bindendes Chaperon interagiert auch mit Chromosomen in der Mitose, wie in vivo wurde, [97] und nachgewiesen mit einer Haarnadelstruktur auf einem Telomer wie explizit bei dem Parvovirus " minute virus of mice " festgestellt wurde [98] .…”
Section: Unbegrenztes Replikationspotentialunclassified